An unusual adverse event with the use of intravenous bolus of promethazine (phenergan) - Singh, Anish; Jain, Mamta; Prakash, Jai; Sharma, Jyoti (International Journal of Research in Medical Sciences, 2017)
The earlier used sedatives like promethazine, pethidine and pentazocine (fortwin) are not commonly used these days but at times they are used especially in periphery for postoperative sedation and in gynecological surgeries and wards. We hereby report an unusual adverse event associated with the use of intravenous bolus of Promethazine. With this case report we want to highlight that if promethazine is to be used for any purpose it should be given preferably intramuscular and if given intravenously, should be diluted and given slowly in a good running cannula.